A new perspective on acoustic rhinometry in terms of standardisation, including the nasal allergen provocation test - Krzych-Fałta, Edyta; Kaczyńska, Olga; Samoliński, Bolesław; Sybilski, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Acoustic rhinometry is an objective nasal patency assessment technique. Its cognitive value means that it plays a major role in the nasal allergen provocation test. The optimisation of the measured values and the interpretation of the results of the test-based values are critical. When the assessment is based on the minimal cross-sectional areas, the volumes for the different segments of the rhinometric curve indicate changes in nasal patency in the nasal allergen provocation test. It seems that the points on the rhinometric curve which correspond to the different waves for the nasal cavity accurately reflect the level of response of the mucous membrane of the nasal cavity to an allergen.